Forgiveness dan Agreeableness pada Pelajar Sekolah Menengah Atas - Verawati Salim; Achmad Irvan Dwi Putra; Yulinda Septiani Manurung (Philanthropy: Journal of Psychology, 2019)
Abstract. This study aimed to know the relationship between the agreeableness and forgiveness. The hypothesis in this study was that there was a positive relationship between agreeableness with forgiveness, in assumption that the higher agreeableness, then the higher forgiveness and the lower agreeableness, then the lower forgiveness itself. The subjects that used in this study were all the rehabilitation patients at SMA Swasta R.A Kartini, in which the population consisted of 120 students. Data obtained from the scale to measure agreeableness and forgiveness. The calculation of the data began by a test prerequisite analysis that consisted of a test of normality and a test of linearity. The data analysis in this study used the Product Moment Correlation with SPSS 19 for Windows. The results of analysis showed the correlation coefficient at r = 0.315 of the significance 0.000 (p < 0.05). Based on the results of this study, the hypothesis is accepted that there is a positive relationship between agreeableness with forgiveness.Keywords: Agreeableness, forgiveness, senior high school, student  Daftar PustakaBeritasatu. (2016). Diejek Di Medsos Remaja Putri Silet tangan lawannya. Jakarta.  Dolan, S. L. 2007. Stress, Self-Esteem, HealthandWork. New York : PalgraveMacmillan.  Fincham, F.D., &Kashdan, T.B 2004. Facilitatingforgiveness: Developinggroupandcommunityinterventions. Buffalo: DeptOfPsychology.  Hall, C. S., &Lindzey. 1985. IntroductiontoTheoriesofPersonality. Singapore: John &Wiley Sons.  Halverson, C. B., &Tirmizi, S. A. 2008. EffectiveMulticulturalTeams : TheoryandPractice. New York : Springer.  Liputan6. (2018). Young Lex pacaran dengan Kathy Indera. Jakarta.  Martin. 2013. Forgivenessis Power: A User sguidetowhyandhowtoforgive. Scotland: FindhornPress.  McCrae, R. R., & Costa, JR, P. T. 2003. Personality in Adulthood: A Five-FactorTheoryPerspectiveSecondEdition. New York: The GuilfordPress.  Mc.Cullough, M.E., Kilpatrick, S.D, Emmons. 2001. Gratitude a Moral Affect. California: Southern MethodistUniversity.  Mc.Cullough, M.E., Adam D. 2006. WritingAbout The BenefitsOf An InterpersonalTransgressionFacilitatesForgiveness. American: Universityof Miami.  Mc.Cullough, M.E., Kilpatrick, S.D, Emmons. 2001. Gratitude a Moral Affect. California: Southern MethodistUniversity.  Monks, F.J., Knoers, A. M. P., Haditono, S.R 2001. Psikologi Perkembangan:Pengantar dalam Berbagai Bagiannya. Yogyakarta: Gadjah Mada UniversityPress.  Reis, H. T., &Sprecher, S. 2009. Encyclopediaof Human Relationships: Vol. 1. Sage.  Ross, S. R., Brose, L. A., Rye. M. S. 2004. ForgivenessandPersonalityTraits. Journal of Personalityand Individual. Vol.39.Santrock, J.W. 2003. Adolescense.Perkembangan Remaja. Edisi Keenam. Jakarta: Erlangga.Santrock, J.W. 2007.Psikologi Perkembangan. Edisi 11 Jilid 1. Jakarta: Erlangga.Soewadji. 2012. Pengantar Metodologi Penelitian. Jakarta: Mitra Wacana Media.Sugiyono. 2013. Metode Penelitian Manajemen. Bandung : Alfabeta.